SOX11 and SOX4 drive the reactivation of an embryonic gene program during murine wound repair - Qi Miao (Nature Portfolio, 2019)
Wounding induces changes in cell identity but the mechanisms regulating this are unclear. Here, the authors show that Sox11/Sox4 expression in the leading edge of wounds converts murine epidermal cells to an embryonic-like state and facilitates repair.